2015
DOI: 10.1097/ede.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Long-and Short-Term Exposure To Air Pollution and Inflammatory/Hemostatic Markers in Midlife Women

Abstract: Background Studies have reported associations between long-term air pollution exposures and cardiovascular mortality. The biological mechanisms connecting them remain uncertain. Methods We examined associations of fine particles (PM2.5) and ozone with serum markers of cardiovascular disease risk in a cohort of midlife women. We obtained information from women enrolled at six sites in the multi-ethnic, longitudinal Study of Women's Health Across the Nation, including repeated measurements of high-sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 43 publications
6
50
0
1
Order By: Relevance
“…The study design and recruitment of participants for the SWAN cohort has been described in detail previously (Green et al, 2016). Six of the seven clinical SWAN sites participated in this specific study of temperature specifically: Chicago, Illinois; Detroit, Michigan; Los Angeles, California; Newark, New Jersey; Oakland, California; and Pittsburgh, Pennsylvania.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and recruitment of participants for the SWAN cohort has been described in detail previously (Green et al, 2016). Six of the seven clinical SWAN sites participated in this specific study of temperature specifically: Chicago, Illinois; Detroit, Michigan; Los Angeles, California; Newark, New Jersey; Oakland, California; and Pittsburgh, Pennsylvania.…”
Section: Methodsmentioning
confidence: 99%
“…If a participant moved (~13% of all women) during the year prior to her visit, exposure data from multiple addresses were weighted based on the time of move when assigning exposure, or evenly weighted if the move date was not available. More details about exposure assignment can be found in Green et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Blood was drawn at each SWAN clinic visit and assayed for CVD markers as described previously (Green et al 2016; Thurston et al 2012). Inflammatory/hemostatic markers examined in this study included high-sensitivity C-reactive protein (hs-CRP), fibrinogen, factor VII coagulant (factor VIIc), tissue-type plasminogen activator antigen (tPA-ag), and plasminogen activator inhibitor Type 1 (PAI-1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated a hazard ratio of 1.08 for dementia, 1.15 for Alzheimer disease, and 1.08 for Parkinson disease admissions per 1 3 increase in annual PM2.5 concentrations. Likewise, Extensive studies have been carried out worldwide for assessing the levels of PM exposure and its associated health impacts (Crouse et al, 2015;Zanobetti et al ,2015;Green et al, 2015;Chung et al, 2015;Hart et al, 2015;Huang et al,(2015) ; Bell et al, 2015). However, limited studies have been reported in India due to lack of PM2.5 data.…”
Section: Introductionmentioning
confidence: 99%